2010
DOI: 10.1152/ajpheart.00891.2009
|View full text |Cite
|
Sign up to set email alerts
|

Structural inhomogeneity and fiber orientation in the inner arterial media

Abstract: The microstructural orientation of vascular wall constituents is of interest to scientists and clinicians because alterations in their native states are associated with various cardiovascular diseases. In the arterial media, the orientation of these constituents is often described as circumferential. However, it has been noted that, just below the endothelial surface, the vascular wall constituents are oriented axially. To further study this reported change in orientation, and to resolve previous observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 44 publications
8
94
2
Order By: Relevance
“…Previous studies have shown that collagen fibers within the arterial media have strong preferential orientation in the circumferential direction (X hh ) while some percentage of fibers are mainly oriented in the axial direction (X zz ) and even smaller percentage in the radial direction (X rr ) [19][20][21][22][23]. Based on those studies, the average orientation for collagen fiber networks in the media [X hh X zz ] was extrapolated to be [0.62 0.37] [20]. The initial network orientation tensor components [X hh X zz X rr ] were, therefore, specified to be [0.6, 0.3, 0.1] 6 [0.039, 0.040, 0.006]-an orientation state close to that measured in Ref.…”
Section: Methods: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that collagen fibers within the arterial media have strong preferential orientation in the circumferential direction (X hh ) while some percentage of fibers are mainly oriented in the axial direction (X zz ) and even smaller percentage in the radial direction (X rr ) [19][20][21][22][23]. Based on those studies, the average orientation for collagen fiber networks in the media [X hh X zz ] was extrapolated to be [0.62 0.37] [20]. The initial network orientation tensor components [X hh X zz X rr ] were, therefore, specified to be [0.6, 0.3, 0.1] 6 [0.039, 0.040, 0.006]-an orientation state close to that measured in Ref.…”
Section: Methods: Modelmentioning
confidence: 99%
“…The initial network orientation tensor components [X hh X zz X rr ] were, therefore, specified to be [0.6, 0.3, 0.1] 6 [0.039, 0.040, 0.006]-an orientation state close to that measured in Ref. [20] and with a small amount of alignment in the r direction to maintain the integrity of the network. A single network was used to represent the combined contribution of the collagen and elastin components, with a volume fraction of 5% [15].…”
Section: Methods: Modelmentioning
confidence: 99%
“…Collagen fibers within the elastin-collagen sheet were generated such that they exhibited strong circumferential orientation, based on the known tissue structure [47][48][49][50][51]. Histological and compositional studies [2,[47][48][49][50][51] show more elastin than collagen within each lamina of the ascending aortic wall. Based on the histological observations of Sokolis et al [51], the overall ratio of elastin-to-collagen within the 2D sheet was set to $1.6.…”
Section: Equationmentioning
confidence: 99%
“…Quantification of clot fiber alignment was achieved through application of an algorithm based on a fast Fourier transform (FFT) that we have previously employed 17 . Briefly, each confocal image was padded with redundant data, a Gaussian decay (standard deviation = 0.25) and two-dimensional Hann window function were applied to minimize edge effects, and the images were transformed into the frequency domain using a two-dimensional FFT (Supplemental Figure 1A-E).…”
Section: Quantification Of Fibrin Fiber Alignmentmentioning
confidence: 99%